Application of presurgical navigated transcranial magnetic stimulation motor mapping for adjuvant radiotherapy planning in patients with high-grade gliomas. (September 2019) - Diehl, Christian D.; Schwendner, Maximilian J.; Sollmann, Nico; Oechsner, Markus; Meyer, Bernhard; Combs, Stephanie E.; Krieg, Sandro M.
Highlights: High-grade gliomas close to motor-eloquent areas are challenging for resection and adjuvant treatment. Preservation of neurologic function is essential for quality of life and outcome. Navigated transcranial magnetic stimulation (nTMS) is a valuable tool to detect primary cortical motor areas. nTMS motor maps can be easily implemented in radiotherapy treatment planning for brain tumors. With nTMS motor maps dose to the primary motor cortex can be reduced without affecting treatment dose. Abstract: Background: Navigated transcranial magnetic stimulation (nTMS) is applied in neurosurgical routine to detect motor-eloquent brain areas for safe resection of high-grade gliomas (HGGs). However, in radiation therapy (RT) planning, the primary motor cortex is not respected yet in target volume delineation. This study evaluates the implementation of nTMS motor mapping in RT planning in patients harboring motor-eloquent HGGs with the aim of reducing dose applications to the motor cortex. Methods: nTMS motor maps of 30 patients diagnosed with motor-eloquent HGGs were fused with RT planning imaging and volumetric modulated RT plans were optimized using nTMS motor maps as an organ at risk (OAR). Doses to nTMS motor maps were evaluated using dose–volume histogram (DVH) parameters. Results: Mean dose (Dmean) to the nTMS motor maps was 42.3 Gy (3.7–61.1 Gy) and was significantly reduced by 14.3% to 37.0 Gy (3.6–55.8 Gy, p < 0.05) when constraining the dose to nTMS motor areas to 45 Gy. Areas within the planning target volume (PTV) were not spared (overlap). Yet, the dose to PTV was not compromised. Even with an additional dose escalation (70 Gy) to the tumor area, nTMS motor maps can be spared by 4.6 ± 3.5 Gy (12.8%, p < 0.05). Conclusions: nTMS motor maps can be easily implemented in standard RT planning and applied for target contouring in RT of HGGs. Doses to motor-eloquent areas can be significantly reduced when considering nTMS motor maps without affecting treatment doses to the PTV. Thus, nTMS could be used as a valuable tool in RT planning.